Geophysical feature of the Mt. Melbourne Area, Antarctica, and preliminary results from the integrated network for monitoring the volcano - Armadillo, E; Bonaccorso, A; Caneva, G; Falzone, P; Ferraccioli, F; Privitera, E; Vittuari, L.; CAPRA, Alessandro; MANCINI, Francesco (Royal Society of New Zealand Bullettin, 2002)
Geophysical features of the Mt. Melbourne area and first results from the integrated network for monitoring the volcano (Antarctica)